Photolytic release of bioactive carboxylic acids from fused pyran conjugates - Conceição, Rafaela (2018)
New ester cages bearing the coumarin (2H-benzopyran-2-one) skeleton with extended π-systems as phototriggers, for glycine and β-alanine, as models of carboxylic acid bifunctional molecules with biological relevance, were evaluated under photolysis conditions at 254, 300, 350 and 419 nm of irradiation in a RPR-100 photochemical reactor. The processes were followed by HPLC-UV detection and 1H NMR with collection of kinetic data. The results showed a correlation between the photolysis efficiency and the increasing extension of the conjugation for both glycine and β-alanine, showing that the 7-aminocoumarin afforded the best results at all wavelengths tested. From a study of the time-resolved fluorescence behaviour, these compounds were also found to exhibit more complex fluorescence decay kinetics. This was attributed to the presence of conjugated and non-conjugated coumarin species.